2011
DOI: 10.1039/c1em10197h
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of nano-ZnO and bulk ZnO suspensions to zebrafish and the effects of sedimentation, ˙OH production and particle dissolution in distilled water

Abstract: With the common application of nanoscale zinc oxide (nZnO) and significant potential for its release directly into aquatic environments, it is urgent to carry out research on ecotoxicological impact of nZnO. The characterization of nZnO, the amount of ˙OH in suspensions in the presence of light and the acute toxicity of nZnO and its bulk counterpart suspensions, as well as the acute toxicity of Zn(2+) solution to zebrafish (Danio rerio) at 96 h were studied. It was found that nZnO aggregated into irregular sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 42 publications
4
46
2
Order By: Relevance
“…The slope (R 2 ) and hazard concentration 5% (with 90% confidence intervals) are indicated. Data from (Adams et al, 2006;Aruoja et al, 2009;Baek and An, 2011;Dasari et al, 2013;Franklin et al, 2007;Heinlaan et al, 2008;Hu et al, 2009;Ivask et al, 2010;Kasemets et al, 2009;Li et al, 2011Li et al, , 2013Ma et al, 2009Ma et al, , 2011Manzo et al, 2013;Mortimer et al, 2010;Nations et al, 2011;Poynton et al, 2011;Wang et al, 2009;Wiench et al, 2009;Xiong et al, 2011;Yu et al, 2011;Zhao et al, 2012;Zhu et al, 2008Zhu et al, , 2009aZhu et al, ,2009b were used for the construction of the SSD. The other invertebrates (for ZnCl 2 ) represent species of sea urchin and protozoa.…”
Section: Effect Of Nanoparticle Dissolution On Ssdmentioning
confidence: 99%
“…The slope (R 2 ) and hazard concentration 5% (with 90% confidence intervals) are indicated. Data from (Adams et al, 2006;Aruoja et al, 2009;Baek and An, 2011;Dasari et al, 2013;Franklin et al, 2007;Heinlaan et al, 2008;Hu et al, 2009;Ivask et al, 2010;Kasemets et al, 2009;Li et al, 2011Li et al, , 2013Ma et al, 2009Ma et al, , 2011Manzo et al, 2013;Mortimer et al, 2010;Nations et al, 2011;Poynton et al, 2011;Wang et al, 2009;Wiench et al, 2009;Xiong et al, 2011;Yu et al, 2011;Zhao et al, 2012;Zhu et al, 2008Zhu et al, , 2009aZhu et al, ,2009b were used for the construction of the SSD. The other invertebrates (for ZnCl 2 ) represent species of sea urchin and protozoa.…”
Section: Effect Of Nanoparticle Dissolution On Ssdmentioning
confidence: 99%
“…Indeed, Yu et al (2011) andXiong et al (2011) showed that under illumination, at concentrations above 10 mg/L, suspensions of ZnO NPs induced hydroxyl radicals ( OH). At the same time, no hydroxyl radical production was detected in case of bulk ZnO particles.…”
Section: Oxidative Stress and The Related Effects Of Nanoparticlesmentioning
confidence: 99%
“…NPs tend to aggregate in the environment and therefore can be eliminated or captured by sedimentation (Zhu et al 2009;Yu et al 2011). Thus it is important to understand the behavior and fate of TiO 2 NPs in aquatic environments in order to elucidate their toxicology.…”
Section: Introductionmentioning
confidence: 99%